The intratumoral distribution influences the prognostic impact of CD68- and CD204-positive macrophages in non-small cell lung cancer. (September 2018) - Li, Zhuo; Maeda, Daichi; Yoshida, Makoto; Umakoshi, Michinobu; Nanjo, Hiroshi; Shiraishi, Kouya; Saito, Motonobu; Kohno, Takashi; Konno, Hayato; Saito, Hajime; Minamiya, Yoshihiro; Goto, Akiteru
Highlights: Tumor stroma is the most suitable area to evaluate TAMs for the prognostification of NSCLC cases. High TAMs infiltration of tumor stroma predicts worse survival rate of NSCLC cases. In lung adenocarcinoma, CD204 is the preferable macrophage marker for prognostification. Abstract: Objective: Tumor-associated macrophages (TAMs) are believed to influence tumor progression and the prognosis of patients. The purpose of this study was to clarify the correlation between the TAM density or location and the clinicopathological features of non-small-cell lung cancer (NSCLC) as well as to explore the prognostic impact of TAMs in NSCLC. Materials and methods: CD68- and CD204-positive macrophages were detected in tumor islets, tumor stroma and alveolar space in 297 patients with NSCLC using immunochemistry. The clinicopathological and genetic factors surveyed were the disease-free survival, age, gender, smoking status, histological type, disease stage, histological grade, pleural invasion, lymph node metastasis, EGFR gene mutations and ALK rearrangements. Results: There were significantly more CD68-positive macrophages than CD204-positive macrophages in each location of the tumor islets, tumor stroma and alveolar spaces, and they were strongly correlated ( P < 0.0001 each). Factors such as male gender, being a smoker, an advanced disease stage and histological grade, positive pleural invasion and node status and wild-type EGFR gene status were significantly correlated with a higher density of CD68- and CD204-positive TAMs in tumor stroma ( P < 0.05 each). In contrast, the age of patients was not correlated with CD68- and CD204-positive TAMs ( P > 0.05 each). Furthermore, survival analysis revealed that a high number of CD68- and CD204-positive TAMs in tumor stroma, but not in tumor islets or alveolar space, was a significant prognostic factor for the disease-free survival time of NSCLC ( P < 0.05, respectively). Moreover, both univariate and multivariate analyses confirmed that higher numbers of CD204-positive TAMs in tumor stroma were an independent worse prognostic predictor for adenocarcinoma. Conclusion: The tumor stroma is the most suitable intratumoral area for the evaluation of TAMs in the setting of the prognostic prediction of NSCLC patients. CD204-positive TAMs are the preferable marker for prognostic prediction in NSCLC, especially in lung adenocarcinoma.